PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR AKTIVA DAN RISIKO BISNIS TERHADAP STRUKTUR MODAL (Studi Empiris Pada Perusahaan Industri Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012 â 2014) - Miftalia Nur Adiyati, 12.05.51.0049; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2016)
The objective of the study is to examine the effect of Profitability, Liquidity, Asset Structure and Business Risk to Capital Structure in an industrial manufacturing company that go public on the Indonesian Stock Exchange. The sampling method using purposive sampling method with the study period of 2012 to 2014. Using data from 17 companies that meet the selection criteria. Relationship and influence between the variables described by using multiple regression analysis. The multiple regression shows that Profitability, Likuidity have significant negative effect on Capital Structure, while Asset Structure significant positive effect on Capital Structure And Business Risk havenât significant positive effect on Capital Structure. Adjusted R Square value of 0,236 can illustrate that the dependent variable is explained by the independent variable variabelitas for 23,6%%, while 76,4% are influenced by the other variables. Keywords: Capital Structure, Profitability, Liquidity, Asset Structure and Business Risk